Performance enhancement of axial concurrent liquidâliquid hydrocyclone separator through optimization of the swirler vane angle - Al-Kayiem, H.H. (Springer, 2020)
Vane angle configuration is considerably affecting the internal flow behavior and separation performance of a concurrent axial inlet liquidâliquid hydrocyclone. This study was carried out to improve the design of the swirl generator by optimizing the vaneâs deflection angle in an oil/water axial inlet hydrocyclone separator. Angles ranging from 37Â° to 75Â° were examined at various operational conditions, including mixture temperature, mixture flow rate, and water-to-oil ratio. Two analysis techniques have been coupled to achieve the aim. First, design of experiment by the response surface method was utilized to generate a combination of run/boundary conditions of swirler vane angles, inlet mixture temperatures, flow rates, and concentrations. The obtained 15 run/boundary conditions were adopted as cases for computational fluid dynamics simulation to determine the separation efficiency, tangential velocity and pressure drop of each case using ANSYS Fluent software. The optimization results show that the swirl generator with a 45Â° deflection angle generated slightly higher tangential velocity compared with higher and lower vane deflection angles. The separation efficiency obtained by using the 45Â° swirl generator was higher than other angles, in spite that the turbulence intensity is slightly higher at 45Â° compared to other vane angles. Â© 2020, The Author(s).